Faith stories - Hickey-Moody, Anna (Manchester University Press, 2023)
This book explores the contention that religious and non-religious people have more in common than we might expect. Anna Hickey-Moody argues that everyone has faith in something and faith is what makes us human. People are both brought together and driven apart by their orientations towards religion and secularism. Across England and Australia, Anna Hickey-Moody has collected community stories about 'what really matters' and what people have faith in. Her findings will take you on many journeys: voyages of escape on small boats, trips into the future in electric cars and art-making on school grounds. Chapters examine how faith can increase and/or reduce people's capacity to act, how it can lead to a deferral of pleasure and a faith in things yet to come. They also explore outsider's worlds: the structures of belonging that sustain social and culturally marginalised people, the kinds of connections fostered through faith and the forms of refusal that faith systems often bring with them. The final chapter examines the other worlds that are created through prayer and creative practice. This book will be of interest to those working in affect studies, religious studies, cultural studies, ethnography, youth studies and sociology.